An indirect comparison of bevacizumab plus cisplatin-gemcitabine and cisplatin plus pemetrexed treatment for patients with advanced first-line non-squamous non-small cell lung cancer in East Asia - John Wen Cheng Chang (2018)
Aims: To compare the relative efficacy of bevacizumab plus cisplatin-gemcitabine chemotherapy (BevCG) with cisplatin plus pemetrexed (CP) in the first-line treatment of advanced or recurrent non-small cell lung cancer (NSCLC) in East Asian patients. In the absence of evidence from head-to-head trials, an adjusted indirect treatment comparison (ITC) approach was selected to compare these treatments. Methods: BevCG and CP treatments have been compared in their relative effects versus their common comparator, the CG treatment. Outcomes from the ITC were used in a statistical model to estimate progression-free survival (PFS) and overall survival (OS) of the two treatments. The non-proportional hazards log-logistic, accelerated failure time model was selected as it provided the best fit. The ITC hazard ratio (HR) was conservatively adjusted to match what was observed between the cumulative hazard functions until the end of the Avastin in Lung trial follow-up period. Results: The ITC analysis suggests that patients treated with Bev-based treatment can expect more favorable outcomes in terms of both PFS and OS (PFS HR=0.71 and OS HR=0.41). Probabilistic sensitivity analyses of PFS and OS HR showed that HR values below 1 are likely to occur in 82% of patients for PFS HR and in 94% of patients for OS HR. Conclusion: BevCG can be considered a more effective therapy than CP for NSCLC patients in East Asia. © 2011 Blackwell Publishing Asia Pty Ltd.